The Impact of Exchange Rate, Inflation, BI7DRR, and Money Supply on the Efficiency of Indonesian Commercial Banks 2018-2024 Period: An Error Correction Model - Muchammad Shubchi Fadhilah Ramadhan; Ajeng Febrianti; Piana Dianawati; Navik Istikomah; Agung Setiawan (Pustaka Digital Indonesia, 2025)
This study is motivated by the urgency to maintain the operational efficiency of Indonesia’s banking sector amid ongoing global economic uncertainty in the post-COVID-19 era, exchange rate volatility, inflationary pressures, and the dynamics of both domestic and international monetary policies. Banking efficiency is a crucial factor in sustaining competitiveness and ensuring the stability of the financial system, especially when facing persistent external pressures. The main objective of this study is to analyze the impact of key macroeconomic variables exchange rate, inflation, the Bank Indonesia 7-Day Reverse Repo Rate (BI7DRR), and money supply on the efficiency of Indonesian commercial banks during the 2018–2024 period. Bank efficiency is measured using the Operating Expenses to Operating Income (OpEx) ratio, which reflects the bank’s ability to manage its operational costs effectively. The study employs the Error Correction Model (ECM) to capture both the short-term and long-term relationships between macroeconomic variables and banking efficiency. The results reveal that exchange rate fluctuations have a significant impact on bank efficiency in the short term, while inflation and money supply exert significant influence in the long term. Conversely, BI7DRR does not show a significant effect in either the short or long term. These findings suggest that banks’ responses to macroeconomic pressures are dynamic and gradual, requiring continuous strategic adjustments. This research contributes to the literature on banking economics in developing countries and provides practical recommendations for policymakers and banking industry stakeholders in formulating monetary policies and operational strategies that are adaptive to volatile economic conditions.